Evaluation of Psychometric Properties of the State and Trait Anxiety Inventory Scale in a Student Sample - Kaupuzs, Aivars; Vazne, Zermena; Usca, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Problems with anxiety are one of the most common presenting problems for university students that affect the mental health. A sample of students (total n=318) were administered Spielberger's State and Trait Anxiety Scale. The demographics of the participants included 38.4% (n = 122) males and 61.6 % (n =196) females, participants ranged in ages from 18 to 25 years old. The average age of respondents was 20.92 (SD =2.07). This study was conducted to evaluate of psychometric properties of the Spielberger's State-Trait Anxiety Inventory form in a student sample. The internal consistency for the STAI was calculated by Cronbach alpha coefficient (α = 0,809). Principal component analysis with Varimax rotation was performed to assess the factor structure for the total sample that yielded four factors. Descriptive statistics were also calculated for the sample. They were found to be moderately trait anxious (M = 38.89, SD = 8.92) with lower state anxiety (M = 35.79, SD = 9.80). The findings of this study suggest that the scale was shown to be reliable and may be valid for measuring anxiety in a student sample.